ISSUES OF ORGANIZATION OF INDEPENDENT WORK OF STUDENTS IN THE SUBJECT OF ECONOMIC AND SOCIAL GEOGRAPHY (Conferencea, 2022)
In this article, the trends of development of society in the Republic of Uzbekistan, the essence of the issues given in the regulation on the organization and control of Independent Education of students in the credit-module system in higher educational institutions, the essence, importance of the content of the organization and preparation of independent work of students on the example of economic and social.